Positive train control, command and communication - Mahfuz, Masharul Bin; Hossain, MD. Shakhawat (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.